The Impact of Strategic Knowledge on Entrepreneurial Performance: An Analytical Research at the Ministry of Education in Iraq - Ekrayyem Hammadi AL-Falloji, Yaseen; Abd Al-Qadeer Ahmed Al-Nuiami, Salah (Journal of Economics and Administrative Sciences, 2024)
The current research aims to study the impact of strategic knowledge on the entrepreneurial performance of a sample of employees in the Iraqi Ministry of Education. Its importance lies in conducting research in the government educational sector. A purposive random sample of 175 individuals was selected based on a data collection questionnaire. Strategic knowledge includes four dimensions (strategic priorities, organizational environment, and organizational capabilities). Entrepreneurial performance addresses four dimensions (proactive planning, leadership indicators, innovation and creativity, efficiency, and effectiveness). The research highlights strategic knowledge in educational administrations to ensure the success of entrepreneurial performance in Iraqi educational institutions. The research problem revolves around the impact of strategic knowledge on entrepreneurial performance practices at the Ministry of Education in Iraq. The results indicate the need for the Iraqi Ministry of Education to adopt a strategic direction through the strategic knowledge of its directorates, which leads to developing the educational landscape and understanding the importance of the appropriate direction to achieve institutional entrepreneurial Performance .Type of paper:- Research paper